2019
DOI: 10.3847/1538-4357/ab4595
|View full text |Cite
|
Sign up to set email alerts
|

An Evolving Broad Iron Line from the First Galactic Ultraluminous X-Ray Pulsar Swift J0243.6+6124

Abstract: We present a spectral study of the ultraluminous Be/X-ray transient pulsar Swift J0243.6+6124 using Neutron Star Interior Composition Explorer (NICER) observations during the system's 2017-2018 giant outburst. The 1.2-10 keV energy spectrum of the source can be approximated with an absorbed cut-off power law model. We detect strong, luminosity-dependent emission lines in the 6-7 keV energy range. A narrow 6.42 keV line, observed in the sub-Eddington regime, is seen to evolve into a broad Fe-line profile in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
(93 reference statements)
5
48
2
Order By: Relevance
“…Therefore, it may be possible that the thermal emission observed at a temperature of about 1.2 keV during Obs-2 is due to the emission from the accretion column while the origin of the lower temperature (0.38 keV) black-body component is due to the possible presence of optically-thick outflows. However, we note that a recent study Jaisawal et al (2019) suggested that, in the ultra-luminous state, the iron line is complex, and if accurately modelled, then the 2 additional black-body components are not required at extreme luminosity. Mushtukov et al (2017) proposed that during super-Eddington accretion, the presence of an accretion envelope plays a key role in the accretion process at extreme mass accretion rates.…”
Section: Broadband Spectroscopymentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, it may be possible that the thermal emission observed at a temperature of about 1.2 keV during Obs-2 is due to the emission from the accretion column while the origin of the lower temperature (0.38 keV) black-body component is due to the possible presence of optically-thick outflows. However, we note that a recent study Jaisawal et al (2019) suggested that, in the ultra-luminous state, the iron line is complex, and if accurately modelled, then the 2 additional black-body components are not required at extreme luminosity. Mushtukov et al (2017) proposed that during super-Eddington accretion, the presence of an accretion envelope plays a key role in the accretion process at extreme mass accretion rates.…”
Section: Broadband Spectroscopymentioning
confidence: 82%
“…These sources might therefore act as an important connecting bridge between the classical X-ray pulsars and ULPs. Jaisawal et al (2019) found a narrow 6.42 keV line when the source was in the sub-Eddington regime. The absence of an iron emission feature in the LAXPC spectra (when the source was accreting at a sub-critical level) could be due to the limited energy resolution of the instrument, which is ∼20% at 6.4 keV (see Yadav et al 2017).…”
Section: Broadband Spectroscopymentioning
confidence: 95%
See 1 more Smart Citation
“…Data below 0.7 keV are not included in our spectral fitting due to observed calibration issues like excess at lower energies. We added a systematic of 1.5% during the spectral analysis, as recommended by the NICER team 3 (Jaisawal et al 2019).…”
Section: Nicermentioning
confidence: 99%
“…The neutron star in these systems usually revolves in a wide, eccentric orbit and is known to accrete matter from the circumstellar disk. The abrupt mass accretion by the neutron star, at the closest approach (periastron), leads to the occurrence of intense X-ray outbursts with luminosity in the range of 10 36 -10 38 erg s −1 (Naik et al 2013;Reig & Nespoli 2013;Wilson-Hodge et al 2018;Jaisawal et al 2019).…”
Section: Introductionmentioning
confidence: 99%